I PLAY AT WORK—ten principles for transforming work processes through gamification - Oprescu, Florin; Jones, Christian; Katsikitis, Mary (Frontiers in Psychology, 2014)
Gamified workplaces could be a positive and innovative solution to addressing contemporary problems in organisations. Such problems include high levels of stress, reduced sense of community, reduced loyalty and rapid changes in the workforce. To better prepare organisations for the future it may be helpful to identify and understand the potential advantages, disadvantages and areas for future research in relationship to the use of gamification for personal and organisational wellbeing. An analysis of research literature across disciplines in combination with expert opinion identified gamified workplaces as a promising strategy for promoting wellbeing. Furthermore, this paper proposes a set of 10 principles as part of a gamification guiding framework (I PLAY AT WORK). In addition to the value of mapping the present for the benefit of the future, there is also considerable value in reshaping core ideas related to the workplaces. Gamified workplaces can provide opportunities for a more vigorous and strategic inter-disciplinary research agenda that can stimulate investments in the area.